Coherence Time Analysis in Semiconducting Hybrid Qubit under Realistic Experimental Conditions. Issue 3 (20th September 2018) - Ferraro, Elena; Fanciulli, Marco; De Michielis, Marco
Abstract: The unavoidable effect of the environmental noise due to nuclear spins and charge traps is included in the study of the hybrid qubit dynamics. Hybrid qubit owes its name to the advantageous combination of manipulation speed of a charge qubit with the longevity of a spin qubit. It consists of three electrons confined through external gate voltages in a double quantum dot and deserves special interest in quantum computation applications due to its advantages in terms of fabrication, control, and only electrical manipulation. The fluctuations of the global magnetic field do not affect the dynamics of the hybrid qubit that is defined in a decoherence‐free subspace. The main sources of decoherence come from local magnetic fluctuations and charge fluctuations. This work is based on the hypothesis that gate voltages are fixed and kept constant while qubit evolves in time. Coherence time of the hybrid qubit is extracted when model parameters take values achievable experimentally in the nuclear‐free isotope 28 Si, natural Si, and GaAs hosts. Abstract : The unavoidable effect of the environmental noise due to nuclear spins and charge traps is included in the study of the hybrid qubit dynamics . The main sources of decoherence come from local magnetic fluctuations and charge fluctuations. Coherence time of the hybrid qubit is extracted when model parameters take values achievable experimentally.